QUANTIFICATION OF TRACTION TO DELIVER THE BUFFALO CALF DURING FORCED CALVING AND ITS INFLUENCE ON BLOOD GAS AND ACID-BASE PARAMETERS
Calculation and measurement of manual traction was recorded during 21 extractions in buffalo dystocias categorized under mild assistance (Mi A